Dual‐Colored Janus Microspheres with Photonic and Plasmonic Faces. Issue 21 (1st May 2022) - Kim, Jong Bin; Kim, Ji‐Won; Kim, Minjung; Kim, Shin‐Hyun
Abstract: Photonic and plasmonic colors, stemming from nanostructures of dielectric materials and metals, are promising for pigment‐free coloration. In particular, nanostructures with structural colors have been employed in stimuli‐responsive Janus microparticles to provide active color pixels. Here, the authors report a simple strategy to produce electro‐responsive Janus microspheres composed of photonic and plasmonic faces for active color change. The photonic microspheres are first prepared by self‐assembly of silica particles in emulsion droplets of photocurable resin. The silica particles form 3D crystalline arrays in the interior and 2D hexagonal arrays on the interface. The emulsion droplets are photocured and the silica particles are selectively removed to make porous photonic microspheres with hexagonal arrays of dimples on the surface. Directional deposition of gold or aluminum on the photonic microsphere develops plasmonic color on the top hemisphere while maintaining photonic color on the bottom hemisphere. Moreover, the metal deposited on one side renders the Janus microspheres electro‐responsive. Therefore, the photonic and plasmonic colors are switchable by the orientation control of the Janus microspheres with an external electric field. The photonic and plasmonic colors are independently adjustable by employing two different sizes of silica particles in core–shell emulsion drops. Abstract : Janus microspheres with photonic and plasmonic faces are created by colloidal self‐assembly in photocurable drops. The colloids spontaneously form 3D crystals in the interior and 2D arrays on the surface. The removal of particles strengthens photonic color and directional deposition of metal renders top hemisphere plasmonically colored. The Janus microspheres provide switching between photonic and plasmonic colors through electric‐field‐driven rotation.